An Evaluation Of Regional Tourism Development Policy: A Case Study Of Sekarsari Hot Spring In Mojokerto City - Dadang Setiyono; Ika Devy Pramudiana; Sri Roekminiati; Slamet Riyadi (International Journal of Humanities and Social Sciences Reviews, 2025)
Regional tourism development is a crucial strategy for driving local economic growth and preserving cultural heritage. However, field conditions often reveal that policy implementation does not always proceed optimally. The Sekarsari Bathing Area in Mojokerto City is one of the tourism sites targeted by development policies, yet it has not demonstrated significant impact on community welfare or tourism attractiveness. This study aims to evaluate the implementation of regional tourism development policies at the Sekarsari site using William N. Dunn’s policy evaluation theory, which includes six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. This research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis from various stakeholders such as the tourism office, site managers, local businesses, and community members. The research instruments were developed flexibly and iteratively according to field dynamics. Data analysis was conducted through data reduction, data display, and conclusion drawing in an interactive manner. The findings reveal that the tourism development policy at Sekarsari has not yet yielded optimal outcomes. The main weaknesses lie in the lack of community participation, uneven distribution of economic benefits, and limited innovation and promotion. Although there have been improvements in basic infrastructure and a modest increase in visitor numbers, the policy has not been fully responsive to local needs. In conclusion, the current policy does not fully meet Dunn’s six evaluation criteria and requires revisions in both strategic planning and technical implementation. This study recommends that future tourism policies be more community-based, inclusive, and adaptive to local contexts. For future research, a mixed-methods approach involving quantitative and geospatial analysis is suggested to strengthen comprehensive evaluative evidence.